Medical Data Privacy Handbook - Gkoulalas-Divanis, Aris.; Loukides, Grigorios; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2015)
This handbook covers Electronic Medical Record (EMR) systems, which enable the storage, management, and sharing of massive amounts of demographic, diagnosis, medication, and genomic information. It presents privacy-preserving methods for medical data, ranging from laboratory test results to doctors comments. The reuse of EMR data can greatly benefit medical science and practice, but must be performed in a privacy-preserving way according to data sharing policies and regulations. Written by world-renowned leaders in this field, each chapter offers a survey of a research direction or a solution to problems in established and emerging research areas. The authors explore scenarios and techniques for facilitating the anonymization of different types of medical data, as well as various data mining tasks. Other chapters present methods for emerging data privacy applications and medical text de-identification, including detailed surveys of deployed systems. A part of the book is devoted to legislative and policy issues, reporting on the US and EU privacy legislation and the cost of privacy breaches in the healthcare domain. This reference is intended for professionals, researchers and advanced-level students interested in safeguarding medical data.
Introduction to Medical Privacy -- A survey of anonymization algorithms for electronic health records -- Differentially Private Histogram and Synthetic Data Publication -- Evaluating the Utility of Differential Privacy -- SECRETA -- Putting Statistical Disclosure Control into Practice -- Utility-constrained Electronic Health Record Data Publishing Through Generalization and Disassociation -- Methods to Mitigate Risk of Composition Attack in Independent Data Publications -- Statistical Disclosure Limitation for Health Data -- A Review of Privacy Preserving Mechanisms for Record Linkage -- Application of Privacy Preserving Techniques in Operational Record Linkage Centres -- Privacy Considerations for Health Information Exchanges -- Managing Access Control in Collaborative Processes for Healthcare Applications -- Automating Consent Management Lifecycle for Electronic Healthcare Systems -- e-Health Cloud -- Preserving Genome Privacy in Research Studies -- Private Genome Data Dissemination -- Threats and Solutions for Genomic Data Privacy -- Medical Image Security -- Privacy Considerations and Techniques for Neuroimages -- Data Privacy Issues with RFID in Healthcare -- Privacy Preserving Classification of ECG Signals in Mobile e-Health Applications -- Strengthening Privacy in Healthcare Social Networks -- Privacy Law, Data Sharing Policies, and Medical Data -- HIPAA and Human Error -- De-identification of Unstructured Clinical Data for Patient Privacy Protection -- Challenges in Synthesizing Surrogate PHI in Narrative EMRs -- Building on Principles -- Epilogue.
Keywords: Database management; Computer security; Data structures (Computer scienc; Medical records -- Data processing; Database Management; Systems and Data Security; Data Structures and Information Theory; Health Informatics